DAMPAK KENAIKAN BAHAN BAKAR MINYAK, TELEPON DAN TARIF DASAR LISTRIK TERHADAP PEREKONOMIAN INDONESIA - Suseno, Djoko (Universitas Slamet Riyadi, 2007)
ABSTRACT In macro view, Indonesia experiences a better economic recovery in recent quarter. After it had experienced a contraction of 13,0 percents in 2005 and grew at 0,39 percents in 2006, Indonesia experienced annual growth of 5,56 percents and 6,23 percents in first and second quarter of 2006 respectively. From an aspect of offer the economic improvement had been recorded in all sectors but agricultural sector. Several sector that had experienced a sufficiently high growth, among the others, were development, transportation and communication, fuel, electricity power, gas, and drinking water sectors and so on. Keywords: price of fuel fossil, telephone tariff and basic tariff of electricity power